Signal Processing A Mathematical Approach (2nd Edition) - Byrne, Charles L. (2014)
This book explains how mathematical tools can be used to solve problems in signal processing. Assuming an advanced undergraduate- or graduate-level understanding of mathematics, this second edition contains new chapters on convolution and the vector DFT, plane-wave propagation, and the BLUE and Kalman filters. It expands the material on Fourier analysis to three new chapters to provide additional background information, presents real-world examples of applications that demonstrate how mathematics is used in remote sensing, and includes robust appendices and problems for classroom use.